Novel method for water purification using activated adsorbents developed from sewage sludge. Issue 33 (14th July 2016) - Elsayed, Yehya; Khamis, Mustafa; Samara, Fatin; Alqaydi, Maitha; Sara, Ziad; Al Zubaidi, Isam; Maruf Mortula, Md.
Abstract: Sewage sludge from Dubai was characterized using inductively coupled plasma and CHN elemental analysis. Selected sludge samples were washed with deionized water until constant conductivity was achieved. The sludge samples (washed and unwashed) were carbonized at 680°C in a semi-static steam environment that was self-generated inside a homemade reaction chamber and with the absence of any external flow. The carbonized materials were then activated by impregnation with sodium hydroxide at 3:1 mass ratio followed by thermal treatment at 680°C in the presence of water. The activated products were characterized using SEM/EDS, CHN elemental analysis, and sorption of nitrogen. The results showed that washing the sludge prior to the carbonization step significantly enhanced the surface area of the final activated product. Activation efficiencies were lower than the carbonization efficiencies. The surface area of the activated adsorbent developed from the washed sludge was 1, 552 m 2 /g compared to 1, 182 m 2 /g of the unwashed sample. Pore size distribution showed slight shift to higher average pore size in the washed sample. The activated adsorbent with the highest surface area was then evaluated for the adsorption of lead. The adsorption capacity of the activated product for lead removal was determined using Toth isotherm. The maximum adsorption capacity for the activated washed sludge was found to be 95 mg/g. The energy contents of the washed raw sludge and the tar by-products that were produced during the carbonization process were found to be 14.8 and 38.1 kJ/g, respectively.